Kolej Antarabangsa Mighty Skills / Abdullah Shahrul Anwar - Shahrul Anwar, Abdullah (Faculty of Business and Management, 2023)
My six-month industrial training at Kolej Antarabangsa Mighty Skills (KAMS) was an incredibly enlightening and memorable experience that has equipped me with a vast array of skills and knowledge that are invaluable to my future career. KAMS is a reputable provider of various Technical and Vocational Education and Training (TVET) programs that are recognized by the Department of Skills Development (DSD). The certifications offered by KAMS range from level 2 to diploma level 4, providing students with a comprehensive and well-rounded education that prepares them for the workforce. During my time at KAMS, I was fortunate enough to work in multiple departments, including administrative, marketing, accounting, operations, human resources, and sales, for both KAMS and its subsidiary, Mighzor Sdn. Bhd. This exposure allowed me to gain a deeper understanding of the inner workings of a TVET institution, as well as acquire a diverse range of skills that will undoubtedly benefit me throughout my career. Specifically, I was able to develop my communication and customer service skills, as well as gain proficiency in accounting software, which will be crucial for any future career in the business industry. In addition to my practical experience, I was also tasked with conducting a comprehensive SWOT analysis of KAMS as part of my report. Through this analysis, I was able to identify the internal factors that the institution can utilize and overcome to ensure its survival, including its well-established reputation and experienced staff. Furthermore, I was able to identify external factors, such as the changing economic landscape and advancements in technology, that are currently affecting the TVET institution. Based on my analysis, I made recommendations for KAMS to utilize both internal and external factors to create a competitive advantage for the college, including investing in new technologies and diversifying its program offerings.